2021
DOI: 10.1001/jamapsychiatry.2020.2493
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Gun Laws—Innovative Interventions to Reduce Gun Violence in the United States

Abstract: In the US, the gun homicide rate is roughly 25 times higher and the gun suicide rate 8 times higher than in other high-income countries. 1 At times, gun violence may seem like a uniquely US crisis that we cannot remedy, insurmountably tied into the very fabric of the nation-in effect, a public health problem of constitutional significance. But simply knowing that the nation is a gun violence outlier among nations is not sufficient in moving the country closer to solutions.When we think of how to prevent or red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The movement calls for police abolition, including disarming and disempowering police institutions; indeed, public health authorities had declared policing (Deivanayagam et al, 2021) and police violence (American Public Health Association, 2018;2020) crises of public health when the movement gained prominence. In line with theories for police abolitionism, it includes often-overlooked calls for agents in systems of public safety that are nonviolent and democratic (such as community-based organizations; Branas et al, 2021). Thus, I-O psychologists can answer public calls to both prevent excessive police violence and increase public health and safety by supporting the change agents that are embedded within and informed about the needs of local communities.…”
Section: Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement calls for police abolition, including disarming and disempowering police institutions; indeed, public health authorities had declared policing (Deivanayagam et al, 2021) and police violence (American Public Health Association, 2018;2020) crises of public health when the movement gained prominence. In line with theories for police abolitionism, it includes often-overlooked calls for agents in systems of public safety that are nonviolent and democratic (such as community-based organizations; Branas et al, 2021). Thus, I-O psychologists can answer public calls to both prevent excessive police violence and increase public health and safety by supporting the change agents that are embedded within and informed about the needs of local communities.…”
Section: Justificationmentioning
confidence: 99%
“…An equity and systems approach explains that community-based organizations can effectively produce systemic outcomes that improve public safety and health. In fact, Branas et al (2021) found that for every 10 additional nonprofit community-building programs per 100,000 residents, there was a 9% reduction in homicide and 6% reduction in violence. These programs included community-led initiatives such as comprehensive early childhood education, youth development, emergency financial assistance in neighborhoods with many foreclosures, career services, and the arts.…”
Section: Why Community-based Organizations?mentioning
confidence: 99%
“…2 Although several policy barriers stand in the way of mobilizing the right data, poor data interoperability across health systems, states, and federal agencies is a critical roadblock as well. 3…”
Section: Prohibited Purchaser Enforcementmentioning
confidence: 99%
“…Beyond laws, we also know that in order to actually protect children in our society, we must invest in the upstream factors that prevent school shootings and other types of gun violence. We know that investing in neighbourhoods and the built environment through the creation of libraries, parks, community centres, and green spaces reduces gun violence and also has other positive impacts on children and the community 12. We know that non-profit, community led programmes, such as career development initiatives and art programmes, are associated with lower rates of gun violence 13.…”
mentioning
confidence: 99%